OVERVIEW OF STRESS COPING STRATEGIES IN STUDENTS WHO COMMIT SELF-HARM - Rosintha Sugesti S.M. Siregar; Togi Fitri A Ambarita (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
This study aims to determine the description of Stress Coping strategies in students who commit self-harm. Based on the results of in-depth interviews with two subjects, data was obtained that each individual has a different way of responding to psychological pressure, especially those related to academic demands, emotional pressure, and traumatic experiences in the past. The first subject (RV) showed that the coping strategies he used were more dominated by aspects of emotion-focused coping, especially in the form of distancing, escape-avoidance, and self-control. Meanwhile, the second subject (KO) showed a more stable and rational coping pattern, although still in the category of emotion-focused coping. Subject KO tended to use ways to avoid pressure by playing games, sleeping, and busying themselves with daily activities. Both subjects had similarities in terms of the lack of use of adaptive coping strategies, such as seeking social support, positive reappraisal. Both did not make spirituality a source of emotional strength, did not interpret pressure as a process of personal growth, and did not establish supportive emotional relationships with people around them. This study emphasizes the importance of psychological, social, and institutional interventions in helping students develop healthy and effective coping skills, especially when facing complex situations of academic crisis and emotional stress.